2021
DOI: 10.1021/acs.inorgchem.1c01275
|View full text |Cite
|
Sign up to set email alerts
|

Triapine Analogues and Their Copper(II) Complexes: Synthesis, Characterization, Solution Speciation, Redox Activity, Cytotoxicity, and mR2 RNR Inhibition

Abstract: Three new thiosemicarbazones (TSCs) HL 1 – HL 3 as triapine analogues bearing a redox-active phenolic moiety at the terminal nitrogen atom were prepared. Reactions of HL 1 – HL 3 with CuCl 2 ·2H 2 O in anoxic methanol afforded three copper(II) complexes, namely, Cu(HL 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 81 publications
2
20
0
Order By: Relevance
“…41 The 1 H NMR spectra show the presence of the Z-isomer (∼20% for IrT, and 8−10% for IrTRe) in solution. 42,43 We tried to do the NMR of the complexes synthesized and purified under complete dark. However, for this system, it remains difficult to get 100% pure E isomer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The 1 H NMR spectra show the presence of the Z-isomer (∼20% for IrT, and 8−10% for IrTRe) in solution. 42,43 We tried to do the NMR of the complexes synthesized and purified under complete dark. However, for this system, it remains difficult to get 100% pure E isomer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The photoinduced E/Z isomerization of the ethenyl/nitrile functionality is well studied and the TSCs are known to undergo such interconversion not only as free ligands but also upon coordination . The 1 H NMR spectra show the presence of the Z -isomer (∼20% for IrT, and 8–10% for IrTRe) in solution. , We tried to do the NMR of the complexes synthesized and purified under complete dark. However, for this system, it remains difficult to get 100% pure E isomer.…”
Section: Resultsmentioning
confidence: 99%
“…Another pseudoreversible process at more positive potentials ( E ° 1/2 0.37 V in Ag/AgCl) has been displayed by the complex, which can be related to this Cu III/II process. Although it has been very difficult to establish a direct and/or accurate comparison with reported data (slight difference of the experimental setup), the obtained redox potential suggests that the Cu­(HL) 2 complex could display resistance to the in vivo reduction . Moreover, some authors have found similar values with copper square planar thiosemicarbazone (NNSS donors) complexes, suggesting also its ineffectiveness role for this redox activity …”
Section: Results and Discussionmentioning
confidence: 89%
“…The acid dissociation constant (pKa) is an elementary parameter in the analysis of drugs and strongly affects their pharmacokinetics and biochemical properties by characterizing the degree of ionization of drug molecules in solution at different pH values ( Besleaga et al, 2021 ). pKa determines the existing form of compounds in the medium and their solubility, lipophilicity, permeability, bioaccumulation, and toxicity ( Konçe et al, 2019 ; Xie et al, 2022 ); these characteristics play a particularly important role in the drug development process ( Bergazin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%